(untitled) (Світ фінансів, 2017)
Тиркало Р. І. Сек`юритизація активів банку: теоретична сутність і особливості здійснення. Розглянуто теоретичну сутність сек’юритизації активів банківських установ. Виявлено ознаки процесу сек’юритизації активів і досліджено етапи його здійснення. Акцентовано увагу на можливості використання вітчизняними банками сек’юритизації активів для підвищення показників адекватності власного капіталу, зниження рівня ризику та диверсифікації джерел фінансування. Tyrkalo R. Securitization of bank assets: theoretical essence and peculiarities of realization. Theoretical essence of bank institution assets’ securitization is examined. Signs of assets’ securitization process are found out and the stages of its realization have been explored. Opportunity of taking advantage of assets’ securitization for increasing ratios of equity capital’s adequacy, decreasing risks level and sources of financing diversification is focused upon.